A formação de uma região: leitura das marcas de colonização italiana nos topônimos do Nordeste do Rio Grande do Sul - Misturini, Bruno (My University, 2019)
This dissertation aims at studying the names of the fifty-eight cities that constitute the Italian Colonization Region in the state of Rio Grande do Sul, southern Brazil. The focus is to understand the motivation for such nomenclatures, considering cultural, linguistic and historical factors. The research corpus was based on pioneering studies by Frosi and Mioranza (2009, 2013), updated by means of document analysis. The city names were split into four categories, regarding the historical phases of the Brazilian Republic. For each toponym, a lexicographic toponymic file was created, based on the methodological proposal by Dick (2004). Subsequently, the analisis focused on the names in relation to the context of their creation. At the end of each chapter, this research presents discussions on the naming criteria, as well as quantitative data on the reasons for the nomenclatures. The results show, in the first place, that there are within the scope of the corpus fourteen names of historical events, seven names of people, seven toponyms with the word “new”, seven names of vegetation features, six names of saints, four toponyms related to the word “city”, four names of human emotions, two of political titles, two of animals, one name inspired by sayings and expressions, one related to housing, one to geographical features, one to minerals, and one to numbers. Furthermore, there are eleven toponyms of physical-environmental nature and forty-seven of anthropo-cultural nature. Regarding the motivations for the nomenclature of the cities in the region, the results included ten names inspired by the history of the Italian immigration in southern Brazil, and ten, to the history of local state politics; Eight names were motivated by vegetation, seven by religion, six by the indigenous culture, and five by the Farroupilha Revolution. In addition, there are four toponyms related to geography, two to climate and weather, two to the local hydrography, and two to the fauna. Finally, there is one name linked to the local history, and another to national politics.
O presente trabalho visa a estudar a motivação e a classificação dos nomes dos cinquenta e oito municípios da Região de Colonização Italiana do Nordeste do Rio Grande do Sul (RCI-RS), tendo como base, principalmente, fatores linguísticos, históricos e culturais. O corpus da pesquisa foi coletado em Frosi e Mioranza (2009, 2013) e atualizado por meio de pesquisa em documentos oficiais. A partir disso, as denominações foram dispostas em quatro grupos distintos, condizentes às fases da República Brasileira. Para cada topônimo, construiu-se uma ficha lexicográfico-toponímica, tendo como base a proposta por Dick (2004), que possibilitou a análise dos nomes, vinculada ao contexto político do período. No final de cada capítulo, apresentou-se uma reflexão sobre os critérios de nomeação, bem como dados quantitativos acerca das motivações e classificações. Os resultados permitem verificar que existem, na RCI-RS, quatorze historiotopônimos, sete antropotopônimos, sete cronotopônimos, sete fitotopônimos, seis hagiotopônimos, quatro poliotopônimos, quatro animotopônimos, dois axiotopônimos, dois zootopônimos, um dirrematotopônimo, um ecotopônimo, um geomorfotopônimo, um litotopônimo e um numerotopônimo. Ademais, constatou-se que há onze topônimos de natureza física e quarenta e sete de natureza antropocultural. No que diz respeito às motivações para a escolha dos nomes desses municípios, apurou-se que há dez voltados à imigração italiana, e dez, à política estadual; oito denominações condizentes à vegetação, sete, à religião, seis, à cultura indígena, e cinco, à Revolução Farroupilha. Além disso, existem quatro topônimos relacionados à geografia, dois, a elementos climáticos, dois, à hidrografia local, e outros dois, à fauna. Por fim, há um nome vinculado à história local, e outro, à política nacional.
Keywords: Toponímia; Onomástica; Italianos; Colonização; Rio Grande do Sul; Toponymy; Onomastics; Italians; Colonization; Rio Grande do Sul (Brazil)